Atlantoaxial stenosis after muscle-preserving selective laminectomy. (June 2022) - Aoyama, Ryoma; Yamane, Junichi; Ninomiya, Ken; Takahashi, Yuichiro; Kitamura, Kazuya; Nori, Satoshi; Suzuki, Satoshi; Matsumoto, Shogo; Kato, Masahiro; Ueda, Seiji; Anazawa, Ukei; Shiraishi, Tateru
Highlights: We experienced four rare cases of C1/C2 stenosis after cervical decompression. We examined the cause for C1/C2 stenosis after muscle-preserving laminectomy. Preoperative small space for a spinal cord was the risk factor for C1/C2 stenosis. Preoperative large atlantodental interval was the risk factor for C1/C2 stenosis. We have revealed indicators of prophylactic decompression at C1/C2. Abstract: There are few reports of degenerative atlantoaxial stenosis and new stenosis after cervical decompression. We experienced four cases of atlantoaxial stenosis after muscle-preserving selective laminectomy. We compared these four cases with no stenosis cases after long-term follow-up of selective laminectomy, as well as healthy subjects. A total of 1205 patients who underwent muscle-preserving selective laminectomy due to cervical disorders were included in this study. Postoperative atlantoaxial stenosis, which needed decompression, appeared in 4 cases, and 30 patients did not have radiological stenosis for more than 10 years after surgery. Twenty healthy volunteers were also used as controls. The radiographic parameters measured were C2-C7 angle, C2-C7 sagittal vertical axis (SVA), C2 slope, C7 slope, C2-C5 angle, C5-C7 angle, C1-C2 angle, and atlantodental interval (ADI). We measured the anterior-posterior (AP) diameters of the spinal cord (SC) and dural tube (Dura) at C1/C2 with sagittal MRI. In the cases of atlantoaxial stenosis, the AP of SC and Dura at C1/C2 were smaller preoperatively, and the residual space for SC (SAC) was also smaller. The preoperative ADI was significantly higher in patients with atlantoaxial stenosis, suggesting preoperative instability at C1/C2. Analysis of the ROC curve showed that patients with a preoperative SAC of less than 3.6 mm and an ADI of more than 1.35 mm were more likely to develop postoperative atlantoaxial stenosis. When we perform a muscle-preserving selective laminectomy, decompression of C1/C2 is suggested when the SAC at C1/C2 is less than 3.6 mm and the ADI is more than 1.35 mm.